Investigating Effects of Solar Proton Events and Forbush Decreases on Ground‐Level Potential Gradient Recorded at Middle and Low Latitudes and Different Altitudes - J. Tacza; A. Odzimek; E. Tueros Cuadros; J.‐P. Raulin; M. Kubicki; G. Fernandez; A. Marun (Space Weather)
Abstract High‐energetic charged particles, such as solar protons, and phenomena such as Forbush decreases are eligible candidates to affect the global electric circuit. These effects have been studied by analyzing disturbances of the potential gradient in ground‐based measurements in fair weather regions. In this paper, we investigate deviations in the potential gradient diurnal curve, during solar proton events, and Forbush decreases, from the mean values obtained in fair weather conditions. In each situation, we select only events which are not accompanied or followed by the other. Using the superposed epoch analysis, in order to enhance the visualization of small effects, we study the potential gradient data recorded between January 2010 and December 2019 at two stations located at low and middle‐latitudes, and at two different altitudes: the Complejo Astronómico El Leoncito (CASLEO), Argentina: 31.78°S, 2550 m a.s.l., and the Geophysical Observatory in Świder (SWIDER), Poland: 52.12°N, 100 m a.s.l., respectively. For intense solar proton events (>100 MeV) we found a statistically significant increase of the potential gradient after solar proton events recorded at CASLEO and no such deviation in the potential gradient recorded at SWIDER. For Forbush decrease events (greater than 4%), no significant deviation of the potential gradient after the start of the event was found in both stations, however for very intense Forbush decreases (>7%) we found an increase of the potential gradient recorded at CASLEO.